The Influence of Student Creativity, Learning Media, Teacher's Teaching Style, Family Environment, and Study Hours on the Learning Outcomes of 11th Grade Students in PKK Subject - Tifa, Nurlatifah; Jolianis; Lovelly Dwinda Dahen (Global Action and Education for Society, 2026)
This study aims to analyze the effect of student creativity, learning media, teacher teaching style, family environment on the learning outcomes of class XI students in PKK subjects at SMKN 1 Simpang Alahan Mati.Using a quantitative approach with associative research methods, data obtained from 74 students selected through stratified random sampling techniques (strata). Analysis was carried out with path analysis techniques.